2020
DOI: 10.1186/s12876-020-01458-x
|View full text |Cite
|
Sign up to set email alerts
|

A severe coronavirus disease 2019 patient with high-risk predisposing factors died from massive gastrointestinal bleeding: a case report

Abstract: Background SARS-CoV-2 is highly infectious and has been a significant public health threat. Despite typical manifestations of illness are dominated by respiratory symptom, some patients have concurrent gastrointestinal manifestations, including nausea, diarrhea, and vomiting. Massive gastrointestinal bleeding, however, has rarely been reported. Case presentation We herein described a case of severe SARS-CoV-2 infected patient with several risk factors for poor prognosis, including male, hypertension, old age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…A well-known complication related to viral illness, altered taste sensation, was present in almost half of the patients (49.8%) with COVID-19[ 22 ]. Chen et al [ 24 ] described a critically ill COVID-19 patient in whom acute respiratory distress syndrome progressed rapidly but who ultimately died from massive GI bleeding even after improvement of the respiratory status. In this patient, the repeat real-time reverse transcriptase PCR SARS-CoV-2 test was positive in stool rather than respiratory specimens, indicating direct and continuous viral invasion of the GI tract.…”
Section: Resultsmentioning
confidence: 99%
“…A well-known complication related to viral illness, altered taste sensation, was present in almost half of the patients (49.8%) with COVID-19[ 22 ]. Chen et al [ 24 ] described a critically ill COVID-19 patient in whom acute respiratory distress syndrome progressed rapidly but who ultimately died from massive GI bleeding even after improvement of the respiratory status. In this patient, the repeat real-time reverse transcriptase PCR SARS-CoV-2 test was positive in stool rather than respiratory specimens, indicating direct and continuous viral invasion of the GI tract.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it should be noted that the most common gastrointestinal manifestations associated with SARS-CoV-2 include nausea, vomiting, abdominal pain and diarrhea. Gastrointestinal bleeding and changes in liver enzymes alanine transferase (ALT) and aspartate transferase (AST) have also been reported [37]. A study in California revealed that GI symptoms affect approximately 31.9% of patients, with anorexia, nausea / vomiting and diarrhea being the most common and mildly described [38].…”
Section: Gastrointestinal Manifestationsmentioning
confidence: 99%
“…A study in California revealed that GI symptoms affect approximately 31.9% of patients, with anorexia, nausea / vomiting and diarrhea being the most common and mildly described [38]. Other studies show reports of patients who presented with gastrointestinal symptoms as the only manifestation of COVID-19 [37,39], a fact that stands out the importance of their understanding. Furthermore, in the province of Zhejiang, China, it was observed that 11% of the cases of COVID-19 had gastrointestinal manifestations, the most common being diarrhea affecting about 70% of the patients with gastrointestinal symptoms and 8% of the total cases.…”
Section: Gastrointestinal Manifestationsmentioning
confidence: 99%
“…Therefore, it should be noted that the most common gastrointestinal manifestations associated with SARS-CoV-2 include nausea, vomiting, abdominal pain and diarrhea. Gastrointestinal bleeding and changes in liver enzymes alanine transferase (ALT) and aspartate transferase (AST) have also been reported [37]. A study in California revealed that GI symptoms affect approximately 31.9% of patients, with anorexia, nausea / vomiting and diarrhea being the most common and mildly described [38].…”
Section: Gastrointestinal Manifestationsmentioning
confidence: 99%
“…A study in California revealed that GI symptoms affect approximately 31.9% of patients, with anorexia, nausea / vomiting and diarrhea being the most common and mildly described [38]. Other studies show reports of patients who presented with gastrointestinal symptoms as the only manifestation of COVID-19 [37,39], a fact that stands out the importance of their understanding. Furthermore, in the province of Zhejiang, China, it was observed that 11% of the cases of COVID-19 had gastrointestinal manifestations, the most common being diarrhea affecting about 70% of the patients with gastrointestinal symptoms and 8% of the total cases.…”
Section: Gastrointestinal Manifestationsmentioning
confidence: 99%